2008
DOI: 10.1104/pp.108.117028
|View full text |Cite
|
Sign up to set email alerts
|

A Third Phytoene Synthase Is Devoted to Abiotic Stress-Induced Abscisic Acid Formation in Rice and Defines Functional Diversification of Phytoene Synthase Genes  

Abstract: We here report on the characterization of a novel third phytoene synthase gene (PSY) in rice (Oryza sativa), OsPSY3, and on the differences among all three PSY genes with respect to the tissue-specific expression and regulation upon various environmental stimuli. The two already known PSYs are under phytochrome control and involved in carotenoid biosynthesis in photosynthetically active tissues and exhibit different expression patterns during chloroplast development. In contrast, OsPSY3 transcript levels are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
249
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(276 citation statements)
references
References 65 publications
18
249
1
1
Order By: Relevance
“…In addition to high light, PSY can be transcriptionally responsive to ABA, salt, drought, temperature, photoperiod, development cues and post-transcriptional feedback regulation . Carotenoid pathway flux can be controlled by multiple PSYs, as is the case for tomato, rice and maize, whereas only a single allele exists in Arabidopsis (Welsch et al , 2008Giorio et al 2008;Li et al 2008a). Multiple homologues of PSY are likely to be somewhat redundant; however, individual PSY alleles are expressed in a tissue-specific manner and only some alleles show a unique response to abiotic stress-induced ABA signalling of PSY gene expression (Li et al 2008b;Welsch et al 2008;Qin et al 2011).…”
Section: Carotenoid Biosynthesis and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to high light, PSY can be transcriptionally responsive to ABA, salt, drought, temperature, photoperiod, development cues and post-transcriptional feedback regulation . Carotenoid pathway flux can be controlled by multiple PSYs, as is the case for tomato, rice and maize, whereas only a single allele exists in Arabidopsis (Welsch et al , 2008Giorio et al 2008;Li et al 2008a). Multiple homologues of PSY are likely to be somewhat redundant; however, individual PSY alleles are expressed in a tissue-specific manner and only some alleles show a unique response to abiotic stress-induced ABA signalling of PSY gene expression (Li et al 2008b;Welsch et al 2008;Qin et al 2011).…”
Section: Carotenoid Biosynthesis and Regulationmentioning
confidence: 99%
“…Carotenoid pathway flux can be controlled by multiple PSYs, as is the case for tomato, rice and maize, whereas only a single allele exists in Arabidopsis (Welsch et al , 2008Giorio et al 2008;Li et al 2008a). Multiple homologues of PSY are likely to be somewhat redundant; however, individual PSY alleles are expressed in a tissue-specific manner and only some alleles show a unique response to abiotic stress-induced ABA signalling of PSY gene expression (Li et al 2008b;Welsch et al 2008;Qin et al 2011). Alternative splicing as well as allelic variation are mechanisms by which to titrate PSY enzyme activity and are likely to underlie a major QTL determinant of flour colour pathway in chloroplasts provides C 20 isoprenoid substrates for carotenoid biosynthesis.…”
Section: Carotenoid Biosynthesis and Regulationmentioning
confidence: 99%
“…The DXS phylogenetic tree (Fig. 3A) showed that the DXS triplication occurred prior to evolution of the grasses, suggesting that grass orthologs may have similar subfunctionalized roles, as shown for the PSY gene family (Li et al, 2008a(Li et al, , 2009Welsch et al, 2008). Therefore DXS3 orthologs in other grass species would be an attractive target for initiating investigations of ratecontrolling steps for endosperm isoprenoid-derived metabolites.…”
Section: Using Maize To Identify Putative Targets In Other Grass Specmentioning
confidence: 99%
“…Maize PSY1 and PSY3 did not respond to light of any spectral type. It was previously demonstrated that PSY3 was associated with carotenogenesis leading to drought and salt-induced ABA biosynthesis in roots (Li et al, 2008); recent work on rice PSY3 showed the rice homolog to have a similar role in rice roots (Welsch et al, 2008). Unlike maize, rice PSY1 and PSY2 are both photoregulated, although blue light was not tested (Welsch et al, 2008), and rice PSY1 is not expressed in endosperm (Gallagher et al, 2004).…”
Section: Psy2 Is Associated With Photomorphogenesismentioning
confidence: 99%
“…It was previously demonstrated that PSY3 was associated with carotenogenesis leading to drought and salt-induced ABA biosynthesis in roots (Li et al, 2008); recent work on rice PSY3 showed the rice homolog to have a similar role in rice roots (Welsch et al, 2008). Unlike maize, rice PSY1 and PSY2 are both photoregulated, although blue light was not tested (Welsch et al, 2008), and rice PSY1 is not expressed in endosperm (Gallagher et al, 2004). Therefore, the ancestral Poaceae PSY was a photoregulated gene; the duplications analyzed in Y1 maize represent losses in the photoregulatory mechanisms and evolution of other features, including the gain-of-function endosperm-specific expression seen for PSY1 in Y1 maize, but absent in its evolutionary ancestor teosinte and other subfamilies of the grasses, including species such as rice.…”
Section: Psy2 Is Associated With Photomorphogenesismentioning
confidence: 99%